Billing rules / global period affect postoperative follow-up practices following total hip arthroplasty. - Philip P Ratnasamy; Oghenewoma P Oghenesume; Peter Y Joo; Jonathan N Grauer (PLoS ONE)
Background Total hip arthroplasty (THA) is a common procedure following which postoperative visits are important to optimize outcomes. The associated global billing period includes the 90 postoperative days (or approximately 13 weeks), during which professional billing is included with the surgery itself. The current study assessed clinical practice patterns relative to the global billing period. Methods Using the PearlDiver M91Ortho dataset, the incidence and timing of Evaluation and Management (E&M) codes in the 26 weeks following THA were assessed. The follow-up visits within and beyond the global billing period, and those conducted by surgeons versus non-surgeon advanced practice providers (APPs) were determined. Results 77,843 THAs were identified. Follow-up visits peaked at postoperative weeks 3, 7, and 14. The greatest week-to-week variation in the number of follow-ups was from weeks 13 to 14 immediately following the global billing period (representing a greater than 4-fold increase in visits.) During the first 13 postop weeks, 73.8% of patients were seen by orthopedic surgeons (as opposed to APPs). In the following 13 weeks, a significantly greater percentage of visits were with surgeons (86.8%, p<0.0001). Conclusions Following the THA global billing period, there was marked increase in the number of follow-ups and transition to a greater percentage being performed by the surgeons. These results provide interesting insight into the potential impact of the billing structure on how practice is pursued.